2011
DOI: 10.1002/hep.24589
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of high-grade dysplastic nodules

Abstract: No definite evidence indicates that the treatment of HGDNs by RFA provides additional long-term overall survival benefit as compared with regular follow-up and timely treatment. The findings of the present study concur with the present American Association for the Study of Liver Diseases guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…However, to our knowledge, no clinical, IHC, and molecular features have been linked with a higher risk of malignant transformation. Consequently, the stratification of this population according to the risk of transformation is impossible . In this line, scientific societies did not propose any guidelines about the treatment and follow‐up of LGDNs or HGDNs .…”
mentioning
confidence: 99%
“…However, to our knowledge, no clinical, IHC, and molecular features have been linked with a higher risk of malignant transformation. Consequently, the stratification of this population according to the risk of transformation is impossible . In this line, scientific societies did not propose any guidelines about the treatment and follow‐up of LGDNs or HGDNs .…”
mentioning
confidence: 99%
“…In contrast to other kinds of early cancer [22], early HCC cannot be completely cured owing to the subsequent hypervascular HCC in the remnant liver due to multicentric hepatocarcinogenesis [6,18,23]. Accordingly, in the present study, half of the patients who underwent liver resection for hypovascular liver nodules had recurrence within 3.6 years after liver resection.…”
Section: Discussionmentioning
confidence: 88%
“…8 However, another study that used a statistical model to estimate the long survival benefit of radiofrequency ablation of high-grade dysplastic nodules reported finding no additional survival benefit associated with this therapy compared with regular follow-ups and timely treatment. 12 At our institute, we assume that livers with nonenhancing lesions and enhancing lesions without washout are at an increased risk for the development of other enhancing HCCs, and even if there is complete removal of marginal lesions, these patients truly will not return to a cancer-free state. In our current study, we found that the presence of nonenhancing lesions and enhancing lesions without washout was an independent factor for the appearance of new lesions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Along with other researchers, we have advocated that the survival benefit achieved by treating such lesions is marginal due to the substantial risk of developing classic HCC in other sites. [12][13][14] Although only a few reports have been published, some of these studies have examined how such premalignant lesions need to be treated when they coexist with a classical HCC. 7 For example, it has been suggested that nonenhancing lesions and enhancing lesions without washout might be able to be removed easily in conjunction with the resection of classical HCC, as this would improve the patients' prognosis.…”
mentioning
confidence: 99%